2018
DOI: 10.3390/ijerph15081729
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Environment Factors and Risk Mapping of Human Cystic Echinococcosis in Western China

Abstract: The study aimed to reveal the risk factors and predict the prevalence of human cystic echinococcosis (CE) in Western China. To do this, we analyzed county-wide data relating to the prevalence of human CE in seven provinces of Western China, along with associated human, natural geographical environmental data. We then used spatial analysis and multiple regression analysis to investigate the correlation between the prevalence of human CE and associated environmental factors and to create a risk map of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 46 publications
3
41
1
Order By: Relevance
“…The survey consisted of a one-time paper and pencil questionnaire to be completed by the students and was conducted in the Tibetan autonomous prefecture of Golog, Qinghai Province, one of the poorest areas in China [24]. Living in the Qinghai-Tibet Plateau with altitudes ranging from 3600 to 4500 meters, people in the region Golog face various challenges including slow social development and limited access to information [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey consisted of a one-time paper and pencil questionnaire to be completed by the students and was conducted in the Tibetan autonomous prefecture of Golog, Qinghai Province, one of the poorest areas in China [24]. Living in the Qinghai-Tibet Plateau with altitudes ranging from 3600 to 4500 meters, people in the region Golog face various challenges including slow social development and limited access to information [14].…”
Section: Methodsmentioning
confidence: 99%
“…Rural Tibetan areas in China are characterized by a high incidence of foodborne parasitic diseases, especially echinococcosis [14]. Studies have shown that a major risk factor associated with echinococcosis is poor handwashing behavior, next to other factors such as living in a rural area, low income, owning dogs, and playing with dogs [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…These articles provide novel insights into the interaction between space and time in the context of each specific infectious disease, providing new perspectives in the understanding of these pathologies and their extent. A total of 11 manuscripts [1,2,3,4,5,6,7,8,9,10,11] were accepted after a single-blind review process by at least two international experts using the journal-specific review guidelines.…”
mentioning
confidence: 99%
“…The different works corresponding to these articles were carried out in different geographical areas of several countries: China [2,5,6,7,8,10], Colombia [4], Ecuador [3], Korea [9], and Taiwan [1]. One of the studies deals with the analysis of an intracellular geometric model [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation